Characterization of the Effect of Melt Treatments on Melt Quality in Al-7wt %Si-Mg Alloys - Uludağ, Muhammet; Cetin, Remzi; Dispinar, Derya; Tiryakioglu, Murat (Mdpi Ag, 2017)
The effects of degassing, holding time and melt additions (Sr, Sr + Ti, Ti, B and B + Sr) on the quality of A356 melts were examined. A total of 120 reduced pressure test samples were collected. Pores in these samples were analyzed via digital image processing to determine the number density of pores as well as the statistical distribution of their sizes. Results showed that in all cases, degassing with argon reduced the number of defects regardless of the additions made to the melts. Moreover, all additions were found to degrade melt quality. The lowest number density of pores in all melts was achieved in melts with no additions that were degassed. In both degassed and non-degassed melts, Sr additions degraded the melt quality significantly. The mechanisms of melt quality improvement or degradation with different melt treatments are discussed in the paper.
Keywords: A356 alloy; degassing; grain refinement; modification; pore size